PERANCANGAN UI/UX ABSENSI KARYAWAN PT. SUMBER BAHAGIA METALINDO DENGAN METODE DESIGN THINKING - Fauziyah, Rizqi; Yunita, Yunita (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2024)
Attendance data is an important factor for the institution or to achieve its objectives, this is related to discipline and affects every employee. Therefore, there is a need to issue data specifically to report and find activities that can be done in real time and good. There are many ways that can be done to achieve a good information system, one of which uses computer technology where the application is with an application-based attendance website. PT Sumber Bahagia Metalindo system which is still in manual attendance using books, data and data recapitulation calculations takes a relatively long time. In addition, data and data shows are larger. Based on the context, an employee attendance information system is created in the PT Sumber Bahagia Metalindo Office. The research method is the method used in the data which includes: research methods, interviews and literature. While the development of software using design thinking which includes: processes such as context analysis, problem discovery and framing, idea and solution generation, creative thinking, sketching and drawing, modeling and prototyping, testing and evaluating. With the attendance results employees can provide assistance in the attendance process, search data and recapitulation, and explore and record attendance data at PT Sumber Bahagia Metalindo.